The Role of E-Leadership in Maximizing Intellectual Capital (Field study on the Directorate of Domestic Trade and Consumer Protection in Aleppo) (Journal of Hama University, 2026)
This research aims to determine the relationship between E-Leadership and Intellectual Capital in Syria in the Ministry of Internal Trade and Consumer Protection (Aleppo Directorate).To achieve this objective, the researcher used a hypothetical-deductive approach to formulate the hypotheses. (85) questionnaires were distributed to the employees that are under study. (79) questionnaires were retrieved and (75) were valid for analysis. a statistical study was conducted to reveal this relationship. The researcher used the correlation coefficient (Person).The study concluded that there is a significant relationship between E-Leadership and Intellectual Capital in the Directorate of Domestic Trade and Consumer Protection in Aleppo. This study also reached a set of recommendations and proposals, Which Would Contribute Positively to Helping Maximizing Intellectual Capital in Public Sector Institutions.